The Impact of Technological Change on New Trade: Evidence from the Container Revolution - Daniel M. Bernhofen; Zouheir El-Sahli; Richard Kneller (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper exploits exogenous features of the 1960s/70s container revolution to estimate the impact of the introduction of refrigerated containers (or reefers) on new trade of temperature sensitive products. Our identification strategy is justified by a historical narrative which suggests that the containerization of bilateral trading routes was exogenous to the growth of trade in `reefer commodities' and stimulated trade in non-traditional (exotic) non-bulk commodities such as pharmaceuticals, photo film and sensitive instruments. Our study combines previously collected data on variations in the container usage on bilateral trade routes with newly collected data on temperature sensitivity and applies them to 5-digit product level trade flows. Our benchmark estimates suggest that the introduction of reefer containers caused an increase in the likelihood of new trade in temperature sensitive products of 9% during 1968 and 1973 and 13% between 1968 and 1978.
Keywords: F13; N70; 330; trade in temperature-sensitive products; extensive margin; impact of refrigerated containers